Evaluating the Effectiveness of Age Restriction on Marriage in Indonesia - Nuruddin, Nuruddin; Wardatul Jannah, Aisyah; Martini, Dwi (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
Child marriage in Indonesia is a multifaceted issue, encompassing religious interpretations, cultural values, and even the influence of technological advancement. A significant factor is the amendment of Indonesian marriage law, which include Article 7, empowering judges to grant marriage dispensation. While this is viewed by some as a solution and a means of child protection through religious and cultural lenses, others see it as a perpetuation of child marriage, contradicting both child protection and marriage laws. This research aims to examine the impact of marriage law in Indonesia, specifically regarding age restrictions and its close association with marriage dispensations in religious courts. Critics argue that this provision has led to an increase in child marriages, with a multitude of biological, physiological, and sociological implications. This study employs normative legal research, incorporating legal, conceptual, and comparative approaches through case analysis and juridical methods. The findings indicate that Marriage Law No. 1 of 1974, along with its amendment—Law No. 16 of 2019, are legally inconsistent with Law No. 23 Year 2002 on child protection. Therefore, legal reform is recommended to raise the marriage age to 21, aligning with biological, psychological, and sociological definitions of adulthood.